Hands-On Natural Language Processing with Python : a Practical Guide to Applying Deep Learning Architectures to Your NLP Applications. - Arumugam, Rajesh (Packt Publishing Ltd, 2018)
This book teaches you to leverage deep learning models in performing various NLP tasks along with showcasing the best practices in dealing with the NLP challenges. The book equips you with practical knowledge to implement deep learning in your linguistic applications using NLTk and Python's popular deep learning library, TensorFlow.